ANALISIS KESALAHAN KEBAHASAAN PADA BUKU TEMATIK TEMA 5 PAHLAWANKU KELAS IV SEKOLAH DASAR - Peni Febriyani; Arum Ratnaningsih; Bagiya Bagiya (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study aims to describe: typographical errors found in the theme book 5 Pahlawanku grade IV elementary school, (2) capital letter errors, (3) punctuation errors, and (4) less subject sentence errors. The method used in this research was descriptive qualitative. The object of this research is the Integrated Thematic Student Book 2013 Curriculum Class IV Theme 5 My Hero. The data collection used were interview techniques, field notes, literature studies, and reading notes. The research instruments used were interview grids, data filter grids, data recording cards, and overall data on linguistic errors. The data analysis method was carried out by the agih method. The data analysis technique used was the erase, replace, and insert technique. The data analysis presentation technique used is an informal technique. From the results of the study, it is known that there are 4 types of errors, namely (1) letter writing errors, there are nine capital letter errors, (2) capital letter errors, there are seven errors, (3) punctuation errors there are fourteen errors, and (4) sentence errors. less subject there are three errors. The most linguistic errors are writing punctuation, there are fourteen errors, and the smallest error is a sentence that lacks the subject, there are three errors